2010
DOI: 10.3174/ajnr.a2281
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Ophthalmoplegia after Endovascular Treatment of Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:Recovery of aneurysm induced CNP after endosaccular coiling has been reported in the literature. The aim of this study was to assess in detail the parameters that affect the outcome after endovascular treatment of ophthalmoplegic aneurysms due CNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…Furthermore, uncertainty surrounds the importance of negative prognostic factors reported in previous series, including old age, general vascular risk factors (tobacco use, high blood pressure, diabetes, chronic alcoholism) [1,23], initial complete palsy [1,7,8,10,13,14,20,25] and long delay before treatment (>3 or 5 days depending on the series) [1,8,15,17,24]. Equally, the positive prognostic value of subarachnoid hemorrhage (SAH) [15] and surgical treatment versus endovascular management of ONP-inducing aneurysm [1,3,7,9,14,19,21,24] remains uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, uncertainty surrounds the importance of negative prognostic factors reported in previous series, including old age, general vascular risk factors (tobacco use, high blood pressure, diabetes, chronic alcoholism) [1,23], initial complete palsy [1,7,8,10,13,14,20,25] and long delay before treatment (>3 or 5 days depending on the series) [1,8,15,17,24]. Equally, the positive prognostic value of subarachnoid hemorrhage (SAH) [15] and surgical treatment versus endovascular management of ONP-inducing aneurysm [1,3,7,9,14,19,21,24] remains uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, although we did not collect data on symptom duration, there is ample evidence that earlier intervention following symptom onset results in the highest likelihood of recovery from cranial or optic neuropathy. 11 This observation may be important because the composition of the aneurysm cohort targeted by PUFS (large, complex neck lesions for which acceptable alternative therapies were lacking) may have contained a bias toward patients with longstanding symptoms.…”
Section: 11mentioning
confidence: 99%
“…The relatively brief follow-up period in this analysis may limit our estimation of the ultimate therapeutic benefit of PED. In a retrospective study of patients with CN palsies related to intracranial aneurysms of any location, 11 the mean length of time between treatment and recovery was 69 days; however, some patients' recoveries took up to 300 days. Moreover, although we did not collect data on symptom duration, there is ample evidence that earlier intervention following symptom onset results in the highest likelihood of recovery from cranial or optic neuropathy.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Several small observational studies have reported improvement in cranial nerve function after aneurysm treatment in those patients presenting with cranial nerve palsy, but no randomized trials have evaluated this practice. [123][124][125][126][127] For patients presenting with oculomotor palsy secondary to posterior communicating aneurysms, several retrospective studies have indicated better resolution with surgery than endovascular therapy [128][129][130] or conservative management. 128 Sudden onset of third nerve palsy in this setting is generally considered an indication of expansion and concern for imminent rupture, necessitating rapid workup and intervention.…”
Section: Clinical Presentationmentioning
confidence: 99%